The effects of early mobilization in mechanically ventilated adult ICU patients: systematic review and meta-analysis - Wang, Lijie; Hua, Yusi; Wang, Luping; Zou, Xia; Zhang, Yan; Ou, Xiaofeng (Frontiers in Medicine, 2023)
Background The effects of early mobilization (EM) on intensive care unit (ICU) patients remain unclear. A meta-analysis of randomized controlled trials was performed to evaluate its effect in mechanically ventilated adult ICU patients. Methods We searched randomized controlled trials (RCTs) published in Medline, Embase, and CENTRAL databases (from inception to November 2022). According to the difference in timing and type, the intervention group was defined as a systematic EM group, and comparator groups were divided into the late mobilization group and the standard EM group. The primary outcome was mortality. The secondary outcomes were ICU length of stay, duration of mechanical ventilation (MV), and adverse events. EM had no impact on 180-day mortality and hospital mortality between intervention groups and comparator groups (RR 1.09, 95% CI 0.89–1.33, p = 0.39). Systemic EM reduced the ICU length of stay (LOS) (MD −2.18, 95% CI −4.22–−0.13, p = 0.04) and the duration of MV (MD −2.27, 95% CI −3.99–−0.56, p = 0.009), but it may increase the incidence of adverse events in patients compared with the standard EM group (RR 1.99, 95% CI 1.25–3.16, p = 0.004). Conclusion Systematic EM has no significant effect on short- or long-term mortality in mechanically ventilated adult ICU patients, but systematic EM could reduce the ICU LOS and duration of MV.